Грибные комары родов Greenomyis и Neoclastobasis (Diptera, Mycetopilidae) фауны СССР - Зайцев, А.И. (Вестник зоологии, 1982)
A taxonomic review of two fungus-gnat genera--Greenomyia B r u n e t t i and Neoclastobasis Ustroverrnova, with special consideration o immature stages morphology and biology. Greenomuia stackelbergi so. n. is described: it differs from other Palearctic representatives o the genusсDy Gisunctive bodu wings, and by genitalic armature characters. Keys to species of the USSR fauna presented.